Impact of DG and D-STATCOM Placement on Improving the Reactive Loading Capability of Mesh Distribution System. (2016) - Gupta, Atma Ram; Kumar, Ashwani
Abstract: In this paper, Distribution Generation (DG) and Distribution STATic COMpensator (D-STATCOM) are optimally placed in mesh distribution systems using sensitivity approaches. The objective of this paper is to improve the reactive loading capability of the network with maintaining voltage profile in an acceptable limit. Optimal locations of DG and D-STATCOM are determined using Voltage Stability Index and Combined Power Loss Sensitivity approaches respectively. The size of DG and D-STATCOM are determined by variational algorithm subjected to minimization of total power loss. In order to quantitatively analyze the impact of DG and D-STATCOM on voltage stability margin, Q-V curves are drawn using continuation power flow method. In this study the impact of simultaneous placement of DG and D-STATCOM is investigated separately for large industrial motor load as well as industrial load. Also, load growth scenario is considered for better planning of the system. The results are obtained on standard IEEE-33 and 69-bus mesh distribution systems to check the feasibility of proposed methodology.